2020
DOI: 10.1093/mnras/staa3432
|View full text |Cite
|
Sign up to set email alerts
|

A low-frequency radio halo survey of the South Pole Telescope SZ-selected clusters with the GMRT

Abstract: The presence of non-thermal electrons and large scale magnetic fields in the intra-cluster medium (ICM) is known through the detection of mega-parsec (Mpc) scale diffuse radio synchrotron emission. Although a significant amount of progress in finding new diffuse radio sources has happened in the last decade, most of the investigation has been constrained towards massive low-redshift clusters. In this work, we explore clusters with redshift z > 0.3 in search of diffuse radio emission, at 325 MHz with the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…We update this relation at GHz and GHz following (van Weeren et al, 2020, hereafter vW20). For this work, we incorporate the compiled literature sample of halos reported by C13 and Martinez Aviles et al (2016), halos in Abell S1121 and Abell 2811 reported by Duchesne et al (2021b), and new halos reported in the literature from 2017 (Parekh et al, 2017; Wilber et al, 2018; Cassano et al, 2019; Brzan et al 2019; Xie et al, 2020; HyeongHan et al, 2020; Giovannini et al, 2020; Wilber et al, 2020; Hoeft et al, 2020; Hoang et al, 2021; Di Gennaro et al, 2020; van Weeren et al, 2020; Raja et al, 2020; Knowles et al, 2021; Raja et al, 2021), with the exception of the halo in ACT-CL J0528.8 –3927 reported by Knowles et al (2021) as its small size and coincidence with a radio-bright BCG suggests a mini-halo. For consistency, cluster masses are obtained from PSZ measurements where available (Planck Collaboration et al 2016c, with some masses obtained from the South Pole Telescope; Song et al, 2012; Reichardt et al, 2013), and only clusters with an SZ-derived mass are used.…”
Section: Resultsmentioning
confidence: 99%
“…We update this relation at GHz and GHz following (van Weeren et al, 2020, hereafter vW20). For this work, we incorporate the compiled literature sample of halos reported by C13 and Martinez Aviles et al (2016), halos in Abell S1121 and Abell 2811 reported by Duchesne et al (2021b), and new halos reported in the literature from 2017 (Parekh et al, 2017; Wilber et al, 2018; Cassano et al, 2019; Brzan et al 2019; Xie et al, 2020; HyeongHan et al, 2020; Giovannini et al, 2020; Wilber et al, 2020; Hoeft et al, 2020; Hoang et al, 2021; Di Gennaro et al, 2020; van Weeren et al, 2020; Raja et al, 2020; Knowles et al, 2021; Raja et al, 2021), with the exception of the halo in ACT-CL J0528.8 –3927 reported by Knowles et al (2021) as its small size and coincidence with a radio-bright BCG suggests a mini-halo. For consistency, cluster masses are obtained from PSZ measurements where available (Planck Collaboration et al 2016c, with some masses obtained from the South Pole Telescope; Song et al, 2012; Reichardt et al, 2013), and only clusters with an SZ-derived mass are used.…”
Section: Resultsmentioning
confidence: 99%
“…We update this relation at ν = 1.4 GHz and ν = 0.15 GHz following van Weeren et al (2020, hereafter vW20). For this work, we incorporate the compiled literature sample of halos reported by C13 and Martinez Aviles et al (2016), halos in Abell S1121 and Abell 2811 reported by Duchesne et al (2017), and new halos reported in the literature from 2017 (Parekh et al, 2017;Wilber et al, 2018;Cassano et al, 2019;Bîrzan et al, 2019;Xie et al, 2020;HyeongHan et al, 2020;Giovannini et al, 2020;Wilber et al, 2020;Hoeft et al, 2020;Hoang et al, 2020;Di Gennaro et al, 2020;van Weeren et al, 2020;Raja et al, 2020;Knowles et al, 2020;Raja et al, 2021), with the exception of the halo in ACT-CL J0528.8−3927 reported by Knowles et al (2020) as its small size and coincidence with a radiobright BCG suggests a mini-halo. For consistency, cluster masses are obtained from PSZ measurements where available (Planck Collaboration et al, 2016c, with some masses obtained from the South Pole Telescope; Song et al 2012;Reichardt et al 2013), and only clusters with an SZ-derived mass are used.…”
Section: Radio Halo P ν -M 500 Scaling Relationsmentioning
confidence: 99%
“…Hence, successfully calibrating and imaging this field would imply that we could apply the techniques on the rest of the sample. [25] and SPT [55] sample used for statistical studies of diffuse emission.…”
Section: The Actpol Samplementioning
confidence: 99%
“…The new studies have resulted in a different class of diffuse emission, such as; radio phoenices and gently re-energized tails (GReETs; [26,52]). The sensitivity of these telescopes have opened up a new observational window which probes lower mass (<4 × 10 14 M ) and higher redshift (z > 0.3) clusters [53][54][55]. Large cluster samples of this nature will help in the refinement of currently existing formation theories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation